ANALYSIS OF 2013 CURRICULUM IMPLEMENTATION USING A SCIENTIFIC APPROACH IN SCIENCE LEARNING IN SMP 24 BENGKULU CITY - Lestari, Indah; Sari, Selfi Novita; Nurfaizi, Egi; Walid, Ahmad (ATTA`DIB, 2023)
SMP 24 Bengkulu City has implemented the curicculum 2013 and students' critical thinking habits when learning science are the emphasis of the curriculum 2013. So that the habit of thinking in a scientific approach is not easy, challenging, and requires preparation. This study aims to find out how the results of the analysis of the science learning process in the imple-mentation of the curicculum 2013 at SMP 24 Bengkulu City. The method used in this study uses descriptive qualitative research methods. The subjects in this study were 2 science teach-ers, the school principal and 10 class IX students. This research was conducted at SMP 24 Bengkulu City in the 2022 academic year, odd semester. So the results obtained in this study came from the results of questionnaires, observations and interviews. The data obtained from this study showed that overall SMP 24 Bengkulu City had implemented the 2013 curriculum very well, but several obstacles were found in its implementation which caused students to become less active during learning.